Potential of Anabaena Azollae Extract as Antimicrobial Agent For Paddy Crop Disease - Nuni Gofar; Andi Diana; Eka Setianingsih (Science and Technology Indonesia, 2018)
The research objective was to test antimicrobial activity from compound produced by A. azollae which symbiosis with Azolla sp. toward microbial test of X. oryzae and Pyricularia oryzae as cause of disease on paddy crop. Sampling of Azolla which symbiosis with A. azollae was done in Azolla cultivation pond at Faculty of Agriculture, Sriwijaya University. The available Azolla was consisted of two types, i.e. Azolla pinnata and Azolla mycrophiylla. The extraction of A. azollae from Azolla leaves was done by method of Ultrasound Assisted Extraction (UAE) using ethyl ester solvent and maseration method using methanol solvent. Test media for bacteria and fungus respectively are Mueller Hilton Agar (MHA) and Sabouraud Dextrose Agar (SDA). The diameter of produced clear zone is an indication of extract’s inhibitory power toward bacteria or fungus. The different of inhibitory zone diameter is compared by using t-test. Analysis of active compounds on Anabaena azollae extract was done by using HPLC. Ethyl acetate or methanol extract of A. azollae which symbiosis with A. pinnata or A. microphylla was capable to inhibit the growth of X. oryzae bacterium and P. oryzae fungus. The dominant compounds containing within extract with probability more than 60% and area of more than 10% are consisted of phytol, hexadecanoate acid and 2-(tert-butyl)-4,6-dimethyl phenol.